Associative learning in people with aphasia: exploring spacing of practice as a potential facilitator. Issue 5 (3rd May 2020) - Wang, Natalie Yu-Hsien; Morris, Julie; Howard, David
ABSTRACT: Background: It remains controversial whether the reduction in associative learning ability previously reported among people with aphasia is specific to linguistic learning or whether the difficulty lies in the formation of new associative learning. Furthermore, an effective associative learning approach that benefits people with aphasia with different profiles of language impairment and levels of severity is yet to be identified. Aims: This study investigates associative learning within linguistic and non-linguistic domains, contrasting the performance of people with aphasia ( n = 11) and two groups of control participants [young ( n = 18) and old ( n = 18)] to identify if, for people with aphasia, reduced associative learning occurs across domains or is specific to the linguistic domain. In addition, the effect of massed and spaced practice is examined to explore potential facilitative learning approaches for people with aphasia. Methods and procedures: Learning of linguistic (word-pairs) and non-linguistic (picture-pairs) material took place separately but follow the same procedures. The study involves pair-association learning, with a study phase (involving massed and spaced practice) followed by an immediate cued recall task to assess learning outcomes. Retention of learning was assessed 2 days post-study, with a delayed recognition task and a delayed cued recall task. Outcomes and results: The findings show that, in cued-recall tasks, despite an overall reduced performance among people with aphasia, patterns of learning largely mirrored the control participants. Word-pairs were better retained than picture-pairs with spaced practice producing better results than massed in both learning conditions. Conclusion: This study advances our understanding of how people with aphasia learn new associations and, regardless of language impairment, associative learning can be facilitated by spaced practice. The findings of the current study highlight the potential importance of adopting spaced practice in clinical settings to maximise outcomes of therapy sessions.